Implantable cardioverter defibrillator and survival after out-of-hospital cardiac arrest due to acute myocardial infarction in Denmark in the years 2001–2012, a nationwide study. Issue 2 (March 2017) - Winther-Jensen, Matilde; Kjaergaard, Jesper; Lassen, Jens F; Køber, Lars; Torp-Pedersen, Christian; Hansen, Steen M; Lippert, Freddy; Kragholm, Kristian; Christensen, Erika F; Hassager, Christian
Aim: The purpose of this study was to describe the implantation of implantable cardioverter defibrillator after out-of-hospital cardiac arrest caused by myocardial infarction in Denmark 2001–2012 and subsequent survival. Methods: The Danish Cardiac Arrest Registry was used to identify patients ⩾18 years surviving to discharge without prior implantable cardioverter defibrillator. Information on cardioverter defibrillator implantation was obtained from the National Patient Registry. Results: We identified 974 myocardial infarction-out-of-hospital cardiac arrest patients surviving to hospital discharge, 130 of these patients (13%) had a cardioverter defibrillator implanted early (⩽40 days post-out-of-hospital cardiac arrest), 58 patients (6%) had late implantable cardioverter defibrillator (41–365 days post-out-of-hospital cardiac arrest). Odds of implantable cardioverter defibrillator implantation within one year were higher in patients receiving cardiopulmonary resuscitation (odds ratio (OR)CPR : 1.99, confidence interval (CI): 1.23–3.22, p =0.01), and Charlson Comorbidity Index level 1, (ORCCI1 : 2.10, CI:1.25–3.49, p <0.01). Odds of a late implantable cardioverter defibrillator was higher in patients undergoing percutaneous coronary intervention (PCI) (ORPCI : 3.67, CI: 1.35–9.97, p =0. 01). An early, but not late implantable cardioverter defibrillator was associated with increased survival (event time ratioEarly ICD : 1.45, CI: 1.11–1.90, p =0.01). Chronic heart failure, higher age groups, Charlson Comorbidity Index levels 1 to ⩾3 and male sex were associated with lower survival. Highest income was associated with higher survival. Conclusion: Cardioverter defibrillator implantation rates in patients surviving an myocardial infarction-out-of-hospital cardiac arrest increased from 14% to 19% over the period. Of the total patient population, 13% had implantation earlier than recommended by guidelines, presumably as primary prevention of sudden cardiac death. Acute PCI and arrest later in the study period (increase one year) were predictors of late cardioverter defibrillator implantation. Early cardioverter defibrillator implantation was significantly associated with a long-term survival benefit, later implantation was not.